Vagus nerve stimulation to treat inflammatory bowel disease: a chronic, preclinical safety study in sheep. Issue 4 (5th February 2019) - Payne, Sophie C; Burns, Owen; Stebbing, Martin; Thomas, Ross; Silva, Angel de; Sedo, Alicia; Weissenborn, Frank; Hyakumura, Tomoko; Huynh, Mario; May, Clive N; Williams, Richard A; Furness, John B; et al.
Aim: Electrical stimulation of the left cervical vagus nerve is a feasible therapy for inflammatory bowel disease (IBD). However, due to the location of the electrode placement, stimulation is often associated with side effects.Methods: We developed a cuff electrode array, designed to be implanted onto the vagus nerve of the lower thorax or abdomen, below branches to vital organs, to minimize off-target effects to stimulation.Results: Following chronic implantation and electrical stimulation, electrodes remained functional and neural thresholds stable, while there were minimal off-target affects to stimulation. No nerve damage or corrosion of stimulated electrodes was observed.Conclusion: This novel electrode array, located on the vagus nerve below branches to vital organs, is a safe approach for the treatment of inflammatory bowel disease.